Macroscopic manifestations - Isaiah, Benjamin Hamilton, author; Bates, Haley, advisor; Voss, Gary, committee member; DiCesare, Catherine, committee member; Wilson, Robert, committee member (Colorado State University. Libraries, 2015)
From the latter half of the twentieth century through the present, scientific experimentation, investigation, and observations allow our species to attain a level of unprecedented understanding of the physical world. Our tools are capable of perceptions more advanced than ever before in human history. Technological advancements make visible that which we have never before been able to witness or comprehend, from the smallest transformation of scale and the subatomic particles composing all things in our physical environment, to the greatest galactic super-clusters that we inhabit. Forms in our Universe are determined by natural physical laws and reactions set into motion far into the past, proceeding from the Big Bang. Events occurring at scales humans perceive to be hyper-microscopic ultimately determine the outcome of realities at our existence as seen through the human observational reference frame. In turn, events occurring at scales exponentially larger than the human scale also govern the realities existing at scales beyond our familiar frame of reference, realms that the Euclidian mind can only perceive as the abyss. Macroscopic Manifestations captures moments and events occurring at transformations of scale both massive and miniscule, frozen in time. This sculptural work forms associations between objects occurring at unfamiliar scales of existence and objects occurring at the familiar human scale of existence. Demonstrating the resemblance innate to objects at every scale of existence, much of the work contained herein is representative of microcosmic and macrocosmic phenomena, and emulates structures apparent in terrestrial marvels, the flora and fauna of Earth.
Keywords: galactic superclusters; particles; subatomic; LHC; CERN; primordial inflation